Relevance Of Primary Molars In Development Of Occlusion In Mixed Dentition - Ana Petcu; A. Maxim; Marinela Pasareanu; Carmen Savin (Romanian Society of Oral Rehabilitation, 2009)
The term "infraocclusion" describes a tooth that lies below the occlusal plane. The infraocclusion is a common eruption disturbance, which constitutes a major clinical problem. It is reported that the prevalence of children with infra-occluded primary molars in the various population ranges from 1.3% to 38.5%. Infraoccluded teeth could have a high potential to malocclusion. In the literature, complications of infraoccluded primary molars were stated as tipping of the neighboring teeth, loss of space, extreme eruption of the antagonist, posterior open bite and rotations in the successor teeth. In the present study, we described a case that presents all temporary molars in infraocclusion and its evolution during a period of surveillance of three years.